New southeastern Nearctic Rhynchelmis (Rhynchelmoides) species and the description of Pararhynchelmis n. gen. (Annelida: Clitellata: Lumbriculidae) - Fend, Steven V.; Lenat, David R. (Zootaxa, 2010)
The first verified records of Rhynchelmis from the southeastern Nearctic represent two new species. Both belong to R. (Rhynchelmoides) (Hrabě) n. comb., which is defined here. Rhynchelmis bolinensis n. sp. resembles other R. (Rhynchelmoides) species with elongate spermathecae, but differs in details of the reproductive structures. Rhynchelmis croatanensis n. sp. is similar in many respects, but the gonads and male and female pores are shifted anteriad by one segment, a character previously unknown within the genus. Pararhynchelmis murdocki n. gen., n. sp. has the spermathecal pores in VIII and IX and male pores in X, and the spermathecae connect to the gut. These characters associate the new species with Rhynchelmis, but the combination of differences in morphology or arrangement of atria, spermathecae, blood vessels and nephridia, and the absence of a proboscis, suggest that it be placed in a related genus. Rhynchelmis bolinensis was collected at several sites in North Carolina, but the other two species are known only from single localities.